COLORS AND THEIR APPEARANCE (World Economics and Finance Bulletin, 2021)
The problem of color is still being studied in many disciplines. If physics is interested in the natural power of color, physiology is the problem of perceiving light through the human eye and turning it into color, psychology is the problem of color perception and its effect on the human psyche, biology is the problem of color in living animals interested in the role and importance.